(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2023)
"Advantages and Disadvantages of the Guided Discovery Approach in Language Teaching" explores the merits and drawbacks of incorporating the guided discovery method into language education. It emphasizes how students actively engage in problem-solving and acquire language skills in meaningful contexts. However, the abstract acknowledges potential challenges, including time constraints and uneven progress among learners. In conclusion, this article examines how guided discovery can enhance language teaching, provided educators carefully consider its advantages and disadvantages to optimize its effectiveness in language acquisition.